Polityka ogłaszania żałoby narodowej w kontekście prawa i zasad savoir-vivre'u: między normami prawnymi a oczekiwaniami społecznymi - Giryn-Boudy, Maria (PRAWO i WIĘŹ, 2025)
The article is an analysis of the phenomenon of national mourning from an interdisciplinary perspective, combining constitutional law, political practice and principles of savoir-vivre. The author attempts to answer questions such as: what formal and informal criteria determine the declaration of national mourning, how social expectations of behaviour during mourning are shaped, and whether political decisions in this regard comply with social and cultural norms. The analysis is based on legislation, case studies and public discourse.